(untitled) (Global Journal of Management and Business Research, 2016)
In 2011 The European Union Tax Commission proposed the establishment of a Financial Transaction Tax (FTT). The FTT was subsequently implemented in France (8/1/12) and Italy (1/1/13). It is also scheduled to be adopted in 9 other European Union states during 2015. Great Britain has thus far failed to accept such a tax. The purpose of the FTT is twofold; minimize and control derivative trading by taxing it, and raise revenues. Opponents of the FTT have suggested that such a tax would increase volatility (i.e., risk) in the securities market and would also lead to a reduction in security trading and a drop in security prices. These are all reasons why Great Britain has thus far refrained from passing the tax.